Color-changing intensified light-emitting multifunctional textiles via digital printing of biobased flavin. Issue 69 (22nd November 2020) - Iyer, Sweta Narayanan; Behary, Nemeshwaree; Guan, Jinping; Orhan, Mehmet; Nierstrasz, Vincent
Abstract : Flavin mononucleotide (biobased flavin), widely known as FMN, possesses intrinsic fluorescence characteristics. Abstract : Flavin mononucleotide (biobased flavin), widely known as FMN, possesses intrinsic fluorescence characteristics. This study presents a sustainable approach for fabricating color-changing intensified light-emitting textiles using the natural compound FMN via digital printing technologies such as inkjet and chromojet. The FMN based ink formulation was prepared at 5 different concentrations using water and glycerol-based systems and printed on cotton duck white (CD), mercerized cotton (MC), and polyester (PET) textile woven samples. After characterizing the printing inks (viscosity and surface tension), the photophysical and physicochemical properties of the printed textiles were investigated using FTIR, UV/visible spectrophotometry, and fluorimetry. Furthermore, photodegradation properties were studied after irradiation under UV (370 nm) and visible (white) light. Two prominent absorption peaks were observed at around 370 nm and 450 nm on K / S spectral curves because of the functionalization of FMN on the textiles via digital printing along with the highest fluorescence intensities obtained for cotton textiles. Before light irradiation, the printed textiles exhibited greenish-yellow fluorescence at 535 nm for excitation at 370 nm. The fluorescence intensity varied as a function of the FMN concentration and the solvent system (water/glycerol). With 0.8 and 1% of FMN, the fluorescence of the printed textiles persisted even after prolonged light irradiation; however, the fluorescence color shifted from greenish-yellow color to turquoise blue then to white, with the fluorescence quantum efficiency values ( φ ) increasing from 0.1 to a value as high as 1. Photodegradation products of the FMN with varying fluorescence wavelengths and intensities would explain the results. Thus, a color-changing light-emitting fluorescent textile was obtained after prolonged light irradiation of textile samples printed using biobased flavin. Furthermore, multifunctional properties such as antibacterial properties against E. coli were observed only for the printed cotton textile while increased ultraviolet protection was observed for both cotton and polyester printed fabrics for the high concentration of FMN water-based and glycerol-based formulations. The evaluation of fluorescence properties using digital printing techniques aimed to provide more sustainable solutions, both in terms of minimum use of biobased dye and obtaining the maximum yield.